Impact of Duration of Mitral Regurgitation on Outcomes in Asymptomatic Patients With Myxomatous Mitral Valve Undergoing Exercise Stress Echocardiography. Issue 2 (10th February 2015) - Naji, Peyman; Asfahan, Fadi; Barr, Tyler; Rodriguez, L. Leonardo; Grimm, Richard A.; Agarwal, Shikhar; Thomas, James D.; Gillinov, A. Marc; Mihaljevic, Tomislav; Griffin, Brian P.; Desai, Milind Y.
Abstract : Background: Significant mitral regurgitation (MR) typically occurs as holosystolic (HS) or mid‐late systolic (MLS), with differences in volumetric impact on the left ventricle (LV). We sought to assess outcomes of degenerative MR patients undergoing exercise echocardiography, separated based on MR duration (MLS versus HS). Methods and Results: We included 609 consecutive patients with ≥III+myxomatous MR undergoing exercise echocardiography: HS (n=487) and MLS (n=122). MLS MR was defined as delayed appearance of MR signal during mid‐late systole on continuous‐wave Doppler while HS MR occurred throughout systole. Composite events of death and congestive heart failure were recorded. Compared to MLS MR, HS MR patients were older (60±14 versus 53±14 years), more were males (72% versus 53%), and had greater prevalence of atrial fibrillation (16% versus 7%; all P <0.01). HS MR patients had higher right ventricular systolic pressure (RVSP) at rest (33±11 versus 27±9 mm Hg), more flail leaflets (36% versus 6%), and a lower number of metabolic equivalents (METs) achieved (9.5±3 versus 10.5±3), compared to the MLS MR group (all P <0.05). There were 54 events during 7.1±3 years of follow‐up. On step‐wise multivariable analysis, HS versus MLS MR (HR 4.99 [1.21 to 20.14]), higher LV ejection fraction (hazard ratio [HR], 0.94 [0.89 to 0.98]), atrial fibrillation (HR, 2.59 [1.33 to 5.11]), higher RVSP (HR, 1.05 [1.03 to 1.09]), and higher percentage of age‐ and gender‐predicted METs (HR, 0.98 [0.97 to 0.99]) were independently associated with adverse outcomes (all P <0.05). Conclusion: In patients with ≥III+myxomatous MR undergoing exercise echocardiography, holosystolic MR is associated with adverse outcomes, independent of other predictors.